Future Trends in Education for a More Sustainable Human Systems Design: The CREATION Project - Ferreira, Ana M.; Savva, Stefania; Souleles, Nicos (My University, 2020)
Europe faces various challenges towards sustainable development. The influx of refugees, youth and gender unemployment, frequent global health threats, spiraling conflict, cultural intolerance, socially marginalized groups, and others are some of the diverse and large-scale social challenges that cannot be ignored. Such reality requires innovative and sustainable responses to address them and puts the economy, the design education sectors and, cultural and creative industries in the spotlight. This paper will reflect upon these ideas and present the CREATION PROJECT, the ReACt Model and the newly created Consortium of seven European organizations that joined to address these issues. It envisages to develop an entrepreneurial skills framework for adult education for the creative and cultural sectors across Europe. The main focus is on bridging the gender gap in entrepreneurship and promoting cultural dialogue. The project will promote the learning of entrepreneurial skills enabling the underrepresented groups to succeed in cultural and arts entrepreneurship. It aspires also contribute to their socioeconomic and cultural sustainability and wellbeing.
Keywords: Co-CREATION; Social design education; Entrepreneurship education; Social innovation; Gender equity; Cultural diversity; Sustainability